A comparison between electronic and printed journals - Trajkovski, Vladimir (ReAttach Therapy International Foundation, 2018)
The number of journals is rapidly rising worldwide. There is public debate about published articles comparing the costs, benefits, and various pros and cons of printed versus electronic full-text journals. The advancement of online journals during recent years has given librarians a powerful new resource to support learning and research. This article explores issues relating to the print publication process and the electronic publication process in order to clarify the unique advantages and disadvantages of each media. Most commercial sites are subscription-based, or allow pay-per-view access. Many universities subscribe to electronic journals to provide access to their students and faculty, and it is generally also possible for individuals to subscribe. An increasing number of journals are now available with open access, requiring no subscription. This is the case with the Journal for ReAttach Therapy and Developmental Diversities. Most working paper archives and articles on personal homepages are free; as are collections in institutional repositories and subject repositories. One of the great advantages of electronic journals is the possibility of acquiring article-level metrics. Printed journals are portable and convenient, don’t require a device to read, have a high graphical resolution (easier to read) and are self-archiving. Printed journals should continue to survive, but only with a decrease in production and changes in content to suit more restricted niches left in the wake of the electronic journals.
Keywords: e-journal, electronic journal, printed journal, academic journal, open access (OA), information technology (IT)